The Potato of the Future: Opportunities and Challenges in Sustainable Agri-food Systems - Devaux, A.; Goffart, J.; Kromann, P.; Andrade-Piedra, J.L.; Polar, Vivian; Hareau, Guy (Springer, 2021)
In the coming decades, feeding the expanded global population nutritiously and sustainably will require substantial improvements to the global food system worldwide. The main challenge will be how to produce more food with the same or fewer resources and waste less. Food security has four dimenespecially the case in Africa wheresions: food availability, food access, food use and quality, and food stability. Among several other food sources, the potato crop is one that can help match all these constraints worldwide due to its highly diverse distribution pattern, and its current cultivation and demand, particularly in developing countries with high levels of poverty, hunger, and malnutrition. After an overview of the current situation of global hunger, food security, and agricultural growth, followed by a review of the importance of the potato in the current global food system and its role played as a food security crop, this paper analyses and discusses how potato research and innovation can contribute to sustainable agri-food systems comparing rural and industrial agri-food systems with reference to food security indicators. It concludes with a discussion about the challenges for sustainable potato cropping enhancement considering the needs to increase productivity in rural-based potato food systems that predominate in low-income countries, while promoting better resource management and optimization in industrial-based agri-food systems considering factors such as quality, diversity of products, health impacts, and climate change effects. Research and innovation options and policies that could facilitate the requirements of both rural and industrial potato-based agri-food systems are described.